Chlorhexidine–Alcohol versus Povidone–Iodine for Surgical-Site Antisepsis - Darouiche, Rabih O; Wall, Matthew J; Itani, Kamal M.F; Otterson, Mary F; Webb, Alexandra L; Carrick, Matthew M; Miller, Harold J; Awad, Samir S; Crosby, Cynthia T; Mosier, Michael C; AlSharif, Atef; Berger, David H (The New England journal of medicine, 2010)
The skin is a source of infection associated with surgery. In this multicenter, randomized trial, the preoperative application of chlorhexidine–alcohol was found to be a more effective skin preparation than povidone–iodine for preventing incisional infections. The preoperative application of chlorhexidine–alcohol was found to be a more effective skin preparation than povidone–iodine for preventing incisional infections. Despite the implementation of preoperative preventive measures, which include skin cleansing with povidone–iodine, surgical-site infection occurs in 300,000 to 500,000 patients who undergo surgery in the United States each year. 1 – 6 Since the patient's skin is a major source of pathogens, it is conceivable that improving skin antisepsis would decrease surgical-site infections. 7 The Centers for Disease Control and Prevention (CDC) recommends that 2% chlorhexidine-based preparations be used to cleanse the site of insertion of vascular catheters. 8 However, the CDC has not issued a recommendation as to which antiseptics should be used preoperatively to prevent postoperative surgical-site infection in the 27 . . .